Use of electronic immunization registry in the surveillance of adverse events following immunization - Sato, Ana Paula Sayuri; Ferreira, Vinícius Leati de Rossi; Tauil, Márcia de Cantuária; Rodrigues, Laura Cunha; Barros, Mariana Bernardes; Martineli, Edmar; Costa, Ângela Aparecida; Inenami, Marta; Waldman, Eliseu Alves (Revista de Saúde Pública, 2018)
OBJECTIVE: To describe adverse events following vaccination (AEFV) of children under two years old and analyze trend of this events from 2000 to 2013, in the city of Araraquara (SP), Brazil. METHODS: This is a descriptive study conducted with data of the passive surveillance system of AEFV that is available in the electronic immunization registry (EIR) of the computerized medical record of the municipal health service (Juarez System). The study variables were: age, gender, vaccine, dose, clinical manifestations and hospitalization. We estimated rates using AEFV as numerator and administered doses of vaccines as denominator. The surveillance sensitivity was estimated by applying the method proposed by the Centers for Disease Control and Prevention. We used Prais-Winsten regression with a significance level of 5.0%. RESULTS: The average annual rate of AEFV was 11.3/10,000 administered doses, however without a trend in the study period (p=0.491). Most cases occurred after the first dose (41.7%) and among children under one year of age (72.6%). Vaccines with pertussis component, yellow fever and measles-mumps-rubella were the most reactogenic. We highlighted the rates of hypotonic-hyporesponsive episodes and convulsion that were 4.1/10,000 and 1.5/10,000 doses of vaccines with pertussis component, respectively, most frequently in the first dose; 60,0% of cases presented symptoms in the first 24 hours after vaccination, however, 18.6% showed after 96 hours. The sensitivity of surveillance was 71.9% and 78.9% for hypotonic-hyporesponsive episodes and convulsion, respectively. CONCLUSIONS: The EIR-based AEFV surveillance system proved to be useful and highly sensitive to describe the safety profile of vaccines in a medium-sized city. It was also shown that the significant increase of the vaccines included in the basic vaccination schedule in childhood in the last decade did not alter the high safety standard of the National Immunization Program.